2003
DOI: 10.1021/np030322r
|View full text |Cite
|
Sign up to set email alerts
|

New Minor Taxane Derivatives from the Needles of Taxus canadensis

Abstract: Seven minor taxane derivatives were isolated for the first time from the needles of Taxus canadensis. Four of these natural taxanes are O-glycosylated (1-4), with 4 being the only reported taxane with a glucose on ring C, and two have a dimethylamino-C-5 side chain (5 and 6). An unusual double bond at C-5(6) has been identified in taxane 7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…[3][4][5][6] T. canadensis, an evergreen shrub distributed in North America, especially in the Quebec region of Canada, is one of the most extensively studied yews and more than 100 new taxanes have been reported. [7][8][9] As a continuation of our phytochemical study on T. canadensis, [10][11][12][13] we investigated the needles and isolated a new 6/8/6-membered taxane with a rare C-12(13)-double bond (1) and a new rearranged 2(3!20)abeotaxane (2) (Fig. 1).…”
mentioning
confidence: 99%
“…[3][4][5][6] T. canadensis, an evergreen shrub distributed in North America, especially in the Quebec region of Canada, is one of the most extensively studied yews and more than 100 new taxanes have been reported. [7][8][9] As a continuation of our phytochemical study on T. canadensis, [10][11][12][13] we investigated the needles and isolated a new 6/8/6-membered taxane with a rare C-12(13)-double bond (1) and a new rearranged 2(3!20)abeotaxane (2) (Fig. 1).…”
mentioning
confidence: 99%
“…Extensive study on the plants of Taxus genus has resulted in the isolation of more than 400 taxanes in the past two decades [4][5][6]. Although many taxoids have been isolated to date, new taxoids continue to be discovered [7][8][9], and some of them could become precursors of paclitaxel and its analogs and some of them showed new activity [10]. Taxus cuspidata is one of the earliest and most extensively studied species [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical shift of HÀC(9) at d(H) 5.05 suggested that the remaining AcO group was attached to C(9), although we did not observe the long-range correlation from HÀC(9) to the corresponding carbonyl Catom. The signal at d(H) 3.01, which exhibited assigned to HÀC (10). Thus, the structure of 1 was characterized as 5a,15-dihydroxy7b,9a-diacetoxy-11(15 !…”
mentioning
confidence: 99%